Clinic0-pathological Profile of Soft Tissue Tumors in a Tertiary care Teaching Hospital in Western India - Khyati Patel; Hrushikesh Surti; Atul Shrivastav (Global Journal of Medicine and Public Health, 2025)
Background Soft tissue tumors (STTs) pose diagnostic challenges due to their histopathological diversity and overlapping clinical features. This study evaluates the histopathological spectrum of STTs in a tertiary care setting to identify demographic trends, anatomic preferences, and tumor behavior. Methods A prospective observational study of 140 STT cases was conducted over 24 months (August 2022–July 2024). Histopathological analysis included hematoxylin-eosin (H&E) staining and classification per the 2020 WHO guidelines. Result Benign tumors predominated (97.1%, n=136), with adipocytic tumors (lipomas) constituting 63.6% (n=89). Malignant tumors were rare (2.9%, n=4) and localized to the lower limb (n=2) and head/neck (n=1). The 31– 40-year age group showed the highest incidence (27.0%, n=38), with no significant gender disparity (female:male ratio=1.06:1). The head/neck (26.4%) and lower limb (25.0%) were the most common sites. A significant association existed between tumor site and histopathological subtype (p<0.001), while age (p=0.52) and gender (p=0.81) showed no correlation with classification. Conclusion In resource-limited settings, histopathology, supported by clinical and radiological findings, is crucial for diagnosing soft tissue tumors. Benign adipocytic tumors predominate, supporting conservative management for asymptomatic cases, while rare malignancies exhibit site-specific clustering (lower limb, head/neck). Strong tumor-site associations (p<0.001) highlight the anatomic context’s diagnostic value. Future molecular profiling and standardized WHO-aligned protocols are needed to refine classification.